Riboflavin status, MTHFR genotype and blood pressure: current evidence and implications for personalised nutrition - McAuley, E.; McNulty, H.; Hughes, C.; Strain, J. J.; Ward, M. (Proceedings of the Nutrition Society, 2016)
Clinical deficiency of the B-vitamin riboflavin (vitamin B2) is largely confined to developing countries; however accumulating evidence indicates that suboptimal riboflavin status is a widespread problem across the developed world. Few international data are available on riboflavin status as measured by the functional biomarker, erythrocyte glutathione reductase activation coefficient, considered to be the gold standard index. One important role of riboflavin in the form of flavin dinucleotide is as a co-factor for the folate-metabolising enzyme methylenetetrahydrofolate reductase (MTHFR). Homozygosity for the common C677T polymorphism in MTHFR, affecting over 10 % of the UK and Irish populations and up to 32 % of other populations worldwide, has been associated with an increased risk of CVD, and more recently with hypertension. This review will explore available studies reporting riboflavin status worldwide, the interaction of riboflavin with the MTHFR C677T polymorphism and the potential role of riboflavin in personalised nutrition. Evidence is accumulating for a novel role of riboflavin as an important modulator of blood pressure (BP) specifically in individuals with the MTHFR 677TT genotype, with results from a number of recent randomised controlled trials demonstrating that riboflavin supplementation can significantly reduce systolic BP by 5–13 mmHg in these genetically at risk adults. Studies are however required to investigate the BP-lowering effect of riboflavin in different populations and in response to doses higher than 1·6 mg/d. Furthermore, work focusing on the translation of this research to health professionals and patients is also required.